Faktor-faktor yang Mempengaruhi Kinerja Karyawan PT. Young Tree Industries - Dewi, Cindy Lusiana (ITB AAS Indonesia Surakarta, 2024)
This study aims to analyze the effect of wages, incentives and social security on employee performance at PT Young Tree Industries, Sukoharjo. The population in this study amounted to 500 sewing employees. The sampling technique used the Slovin formula, so that the sample used in this study was 84 respondents. Hypothesis testing in this study used statistical analysis a ssisted by the SPSS version 26 program which includes the classical assumption test, multiple linear regression, coefficient of determination (R2), t test, and F test. The results showed that the wage variable had a significant effect on employee performance with a t value of 0.041